The Semiotics of Humiliation - Andi Rachmawati Syarif; Nursidah Nursidah (Institut Agama Islam Negeri Palopo, 2020)
Being almost inseparable from human being, ‘Humiliation’ and ‘dignity’ must be considered as much more universal substance. Its counterpart must be regarded as having the same level of universality. However, is the fact that the form of both ‘dignity’ and ‘humiliation’ differ so much around the world, that the two terms probably represent the best argument for that there are big differences between cultures and nations. Since the experience of humiliation does not necessary result in an immediate feeling of being humiliated. Thus one of the core challenges is to find the solution of how ‘humiliation’ on the one hand represents something universal and on the other hand is the best argument for non-universality in the world. In this sense, the essay seems to be much easier to say something about the cause for humiliation instead of its effect on the victim. Yet, this essay attempts to point out how these terms might be understood in attempt at making them meaningful in itself and fruitful for empirical investigation.